The impact of physical activity and diet in the treatment of hypothyroidism: A systematic review - Zduńczyk, Wiktoria; Dobosz, Anna; Dubińska, Michalina; Paduch-Jakubczyk, Wiktoria; Bilska, Wiktoria; Ciułek, Urszula (Quality in Sport, 2024)
Introduction and Objective: Thyroid diseases constitute a significant health challenge of the 21st century. Due to the growing awareness of the accompanying symptoms and the impact of the proper functioning of the thyroid gland on the overall condition of the body, patients show increasing interest in therapeutic methods. The main aim of the article is to present the impact of physical activity and proper diet on the management of patients with hypothyroidism. Review and Methods: Review and summary of studies and meta-analysis of studies available in open-source format on Google Scholar, Web of Science and PubMed. Abbreviated Description of the State of Knowledge: Hypothyroidism is a clinical condition characterized by the insufficient production of thyroid hormones by the thyroid gland. This hormonal deficiency leads to a generalized decrease in metabolic processes. Clinically, hypothyroidism is diagnosed based on elevated serum levels of thyroid-stimulating hormone (TSH) and decreased levels of free thyroxine (T4). Prevalent symptoms include fatigue, constipation, weight gain, cold intolerance, depression and dry skin. Effective management typically involves hormone replacement therapy with synthetic thyroxine. Summary: Hypothyroidism is a complex disease influenced by many factors. A multidisciplinary approach is recommended in its treatment, including pharmacological treatment, diet and appropriately selected physical activity. Early diagnosis and treatment are essential to improve the physical and mental condition of patients.